Südtirols Autonomie gestern, heute und morgen 50 Jahre Zweites Autonomiestatut: Rück-, Ein- und Ausblicke - Obwexer, Walter; Happacher, Esther (Grenz-Räume, 2023)
In 1972, the Second Statute of Autonomy came into force as the central constitutional foundation of South Tyrol's autonomy and thus of the protection of the German and Ladin minorities in South Tyrol. With reference to selected areas, such as competences, financial autonomy, language use, education and relations with other autonomies, this book shows how the Statute has proved itself in practice. Legal solutions for the rapidly changing requirements in law and society, for example through digitalisation, are also examined, as are South Tyrol's relations with the region of Trentino-Alto Adige/Südtirol, municipalities and Europe. With contributions by Andrea Ambrosi | Siegfried Brugger | Paolo Coppola | Matteo Cosulich | Elena D'Orlando | Sigrun Falkensteiner | Martha Gärber | Esther Happacher | Thomas Mathà | Walter Obwexer | Gianfranco Postal | Martha Stocker | Helmut Tichy | Roberto Toniatti | Alice Valdesalici | Karl Zeller